An Investigation for Large Volume, Focal Blood-Brain Barrier Disruption with High-Frequency Pulsed Electric Fields - Melvin F. Lorenzo; Sabrina N. Campelo; Julio P. Arroyo; Kenneth N. Aycock; Jonathan Hinckley; Christopher B. Arena; John H. Rossmeisl; Rafael V. Davalos (MDPI AG, 2021)
The treatment of CNS disorders suffers from the inability to deliver large therapeutic agents to the brain parenchyma due to protection from the blood-brain barrier (BBB). Herein, we investigated high-frequency pulsed electric field (HF-PEF) therapy of various pulse widths and interphase delays for BBB disruption while selectively minimizing cell ablation. Eighteen male Fisher rats underwent craniectomy procedures and two blunt-tipped electrodes were advanced into the brain for pulsing. BBB disruption was verified with contrast T1W MRI and pathologically with Evans blue dye. High-frequency irreversible electroporation cell death of healthy rodent astrocytes was investigated in vitro using a collagen hydrogel tissue mimic. Numerical analysis was conducted to determine the electric fields in which BBB disruption and cell ablation occur. Differences between the BBB disruption and ablation thresholds for each waveform are as follows: 2-2-2 <semantics>μ</semantics>s (1028 V/cm), 5-2-5 <semantics>μ</semantics>s (721 V/cm), 10-1-10 <semantics>μ</semantics>s (547 V/cm), 2-5-2 <semantics>μ</semantics>s (1043 V/cm), and 5-5-5 <semantics>μ</semantics>s (751 V/cm). These data suggest that HF-PEFs can be fine-tuned to modulate the extent of cell death while maximizing peri-ablative BBB disruption. Furthermore, numerical modeling elucidated the diffuse field gradients of a single-needle grounding pad configuration to favor large-volume BBB disruption, while the monopolar probe configuration is more amenable to ablation and reversible electroporation effects.